2016
DOI: 10.1016/j.jgo.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric assessment with management in cancer care: Current evidence and potential mechanisms for future research

Abstract: Older adults with cancer represent a complex patient population. Geriatric assessment (GA) is recommended to evaluate the medical and supportive care needs of this group. “GA with management” is a term encompassing the resultant medical decisions and interventions implemented in response to vulnerabilities identified on GA. In older, non-cancer patients, GA with management has been shown to improve a variety of outcomes, such as reducing functional decline and health care utilization. However, the role of GA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 31 publications
1
80
0
1
Order By: Relevance
“…34,35 Unfortunately, in patients with cancer, there are limited data to support GA-based interventions in busy oncology clinics. 36 That being said, some of these interventions are simple in nature and are used by many clinicians treating HNSCC and other cancer types already. A panel of experts in Geriatric Oncology, using a Delphi consensus technique, published recommendations on GA-guided interventions among older adults with cancer.…”
Section: Methodsmentioning
confidence: 99%
“…34,35 Unfortunately, in patients with cancer, there are limited data to support GA-based interventions in busy oncology clinics. 36 That being said, some of these interventions are simple in nature and are used by many clinicians treating HNSCC and other cancer types already. A panel of experts in Geriatric Oncology, using a Delphi consensus technique, published recommendations on GA-guided interventions among older adults with cancer.…”
Section: Methodsmentioning
confidence: 99%
“…911 Implementing geriatric assessment (GA) with targeted management interventions to address specific impairments may help to improve older adults’ tolerance of therapy and cancer-related outcomes. 12 A few select studies in geriatric oncology have evaluated the impact of GA on change in treatment plan and GA management interventions in a non-randomized fashion. 1319 Although GA with management interventions has not yet been formally evaluated in the older cancer population in randomized studies, multiple studies in the non-cancer setting demonstrate benefit from GA management, suggesting potential benefit in the oncology setting as well.…”
Section: Introductionmentioning
confidence: 99%
“…2034 GA can identify specific impairments, such as cognitive impairment or limited social support, and targeted management interventions can be used to support these vulnerabilities in patients receiving cancer therapy. 12 GA management interventions are utilized frequently by geriatricians in the non-cancer population with the goal to reverse or provide support to areas of impairment identified on GA. An example of a targeted management intervention based upon GA impairment is implementing physical therapy and home safety evaluations for individuals with impaired physical function or falls. GA with targeted management interventions has been studied extensively in the general geriatrics population and have been shown to reduce mortality, 28,31 hospitalizations 32 and functional decline.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated that GA information can influence an oncologist’s treatment decisions in older cancer patients. 4648 In six of the ten studies in a systematic review by Hamaker et al, the initial cancer treatment plan was modified in 39% of patients after GA evaluation. 47 Non-oncological interventions based on the GA were recommended for a median of 83% of patients.…”
Section: Discussionmentioning
confidence: 99%